Glutathione Activates Type III Secretion System Through Vfr in Pseudomonas aeruginosa - Zhang, Yani; Zhang, Chao; Du, Xiao; Zhou, Yun; Kong, Weina; Lau, Gee W.; Chen, Gukui; Kohli, Gurjeet Singh; Yang, Liang; Wang, Tietao; Liang, Haihua (Frontiers in Cellular and Infection Microbiology, 2019)
Glutathione is the most abundant antioxidant in all living organisms. We have previously identified a deletion mutant of glutathione synthetase gene (gshB) in Pseudomonas aeruginosa caused a decreased expression of type III secretion system (T3SS), but the mechanism remains elusive. In this study, a comprehensive transcriptome analysis of the ΔgshAΔgshB mutant lacking the ability to synthesize glutathione (GSH) in P. aeruginosa was used to elucidate the role of glutathione in the pathogenesis of P. aeruginosa. The transcriptome result shows that the expression of some secretion systems and regulatory genes were impaired, including type III secretion system (T3SS) and type VI secretion system (T6SS). ΔgshAΔgshB caused a reduction in virulence in a mouse model of acute pneumonia, and also showed weakened swimming and swarming motilities and decreased biofilm formation. These results suggest that the levels of intracellular GSH modulate virulence properties of P. aeruginosa, and is important for full cytotoxicity and host infection. Under T3SS inducing conditions, the expression of T3SS was induced by glutathione in the wild-type strain PAO1 and ΔgshAΔgshB, but not in Δvfr mutant. Genetic complementation of the Δvfr mutant restored this phenotype. When all the cysteine residues in Vfr protein were substituted with alanine, the expression of T3SS could not be induced by GSH, suggesting that GSH regulate T3SS gene through Vfr. Further experiments revealed that H2O2-treated Vfr exhibited decreased free thiol content compared to untreated control, indicating that Vfr was oxidized by H2O2. Importantly, glutathione restored the oxidized Vfr to reduced state. Our results demonstrate that glutathione serves as an intracellular redox signal sensed by Vfr to upregulate T3SS expression in P. aeruginosa. Our work provides new insights into the role of GSH in P. aeruginosa pathogenesis.